Towards an alcohol‐free process for the production of palm phytonutrients via enzymatic hydrolysis of crude palm oil using liquid lipases. (23rd June 2022) - Adiiba, Siti Hanifah; Chan, Eng‐Seng; Lee, Yee Ying; Amelia,; Chang, Mun Yuen; Song, Cher Pin
Abstract: BACKGROUND: Crude palm oil (CPO) is rich with phytonutrients such as carotenoids and tocols which possesses many health benefits. The aim of this research was to develop a methanol‐free process to produce palm phytonutrients via enzymatic hydrolysis. In this work, triacylglycerol was hydrolyzed into free fatty acids (FFAs) using three different types of liquid lipases derived from Aspergillus oryzae (ET 2.0), Aspergillus niger (Habio) and Candida antartica (CALB). RESULTS: ET 2.0 was found to be the best enzyme for hydrolysis. Under the optimum condition, the FFA content achievable was 790 g kg −1 after 24 h of reaction with 1:1 water‐to‐oil mass ratio at 50 °C and stirring speed of 9 ×  g . Furthermore, with the addition of 2 g kg −1 ascorbic acid, it was found that 98% of carotenoids and 96% of tocols could be retained after hydrolysis. CONCLUSION: This work shows that enzymatic hydrolysis, which is inherently safer, cleaner and sustainable is feasible to replace the conventional methanolysis for the production of palm phytonutrients. © 2022 The Authors. Journal of The Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.